Senior synonyms for three Neotropical birds described by Louis Vieillot based on Félix de Azara (Passeriformes: Thraupidae, Tyrannidae, Tityridae) - Smith, Paul; Pacheco, J. Fernando; Bencke, Glayson Ariel; Aleixo, Alexandre (Zootaxa, 2018)
The nomenclatural history of three species described by Vieillot based on the descriptions of Félix de Azara is examined. Adherent to the Principle of Priority under the International Code of Zoological Nomenclature, old available names and senior synonyms are identified for the thraupid Uniform Finch Haplospiza plumbea (Vieillot, 1818a); tyrannid Tropical Pewee Contopus sylvestris (Vieillot, 1816); and tityrid White-winged Becard Pachyramphus cyanocephalus (Vieillot, 1816). These names were based respectively on Azara’s Number 111 “Pico de punzón obscuro aplomado”, Number 168 “Tachurí obscurito mayor” and Number 217 “Batará obscuro y negro”. It is recommended that these names should all be suppressed as nomina oblita in the interests of stability.